PECULIARITIES OF LAND MANAGEMENT WORKS ON THE TERRITORY OF MILITARY BASES - Savkov, P.; Levinskova, N.; Kryth, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article focuses on the main legal aspects of the land registry system in Ukraine. Research allowed to identify the shortcomings of the existent, inefficient land registry system, which significantly increase the conflict potential of land matters. The article also covers the preconditions needed for the establishment of an efficient land registry system based on the lessons learned from land surveying activities of the Ministry of Defense. Moreover, it provides a comprehensive description of the current state of the national land registry system of Ukraine. The paper highlights factors enabling the development of a cohesive system of measures, that would allow to significantly improve management of the land registry system of Ukraine. A list of reasons has been provided, justifying a lack of an all-encompassing registration of the military land parcels of the Ministry of Defense of Ukraine. Besides, many other topical issues related to the military land were identified, including systematic shortcomings that intervene with the comprehensive and legal usage of real estate assets of the Armed Forces of Ukraine. In order to ensure that the real estate and land parcel management system conforms to the law, preconditions for the establishment of a computerized military land and real estate registration system were identified. Research findings included suggestions related to the establishment of land management, registry and land registration center in the structure of MOD, which would deal with issues related land management, registry and land registration. To ensure direct control and timely response such center would have subordinated detachments. The article provides a list of suggestions for the establishment of an efficient control over the land fund of the Armed Forces of Ukraine, which will not only simplify the process of stock taking, but also will speed up the process of land parcel transfer to the Ministry of Defense of Ukraine.
Keywords: land registry, land parcel, registry map, land management activities, military base